KEDUDUKAN NASKAH AKADEMIK DALAM PENAFSIRAN KETENTUAN-KETENTUAN DALAM UNDANG-UNDANG - Eko Supriyanto (Yuridika, 2017)
Even though an text academic was required in the bill, but an text academic is not necessarily used as an instrument by the legislators in shaping legislation and interpret the provisions of the law by the Constitutional Court. Based on consideration of the Constitutional Court the existence of an text academic was not binding on legislators and text academic as a material law also does not bind the Constitutional Court for use in interpreting the provisions of the law. So interpretation is one way to perfect the constitution. The interpretation that has binding power is the judicial interpretation. But in making that interpretation, the court is not doing it as a special activity or individually but through its decisions. Therefore, in relation to the constitutional interpretation made by the Constitutional Court in the case of decisions of the Constitutional Court is essentially the forms of judge interpretation and contains binding interpretations on various constitutional provisions relating to the case filed.